The Pre–Historic Proboscideans of Nepal - Shrestha, Ramesh (Journal of Natural History Museum, 2015)
Although Nepal is one of the native habitats of the present day species of the Asian elephant, Elephas maximus; it is also an important seat of early Proboscidean evolutionary grounds. Up to now four families and within them seven species of Proboscideans are recorded from Nepal in the forms of different fossils. Out of the total known Proboscideans throughout the world and Indian sub–continent, Nepal had approximately 3.86% and 14% respectively. This fact undoubtedly indicates that Nepal has remained an important place with perfect ecological conditions for the advance of elephants since pre–historic times. J. Nat. Hist. Mus. Vol. 28, 2014: 137-141